Synthesis and Antimycobacterial Activity of 3-(Arylaminomethyl)-5- (Pyridin-4-yl)-1,3,4-Oxadiazole-(3H)-thi-2-One Derivatives Against Mycobacterium Tuberculosis H37rv Strain - Asif, Mohammad; Imran, Mohd (Current Bioactive Compounds, 2021)
Background: Oxadiazole derivatives are the biologically active heterocyclic compounds. Thus, we synthesized a series of Mannich bases, 3-(arylaminomethyl)-5-(pyridin- 4-yl)-1,3,4-oxadiazole-(3H)-thi-2-one derivatives(3a-3g) were synthesized from Isoniazid [INH (1)], a first line antimycobacterial drug, and these compounds were evaluated as antimycobacterial agents. Methods: The INH was reacted with potassium hydroxide and carbon disulfide to give 5-(pyridin- 4-yl)-1,3,4-oxadiazole-2(3H)-thione (2), followed by reacting compound 2 with appropriate aromatic amines in the presence of formaldehyde to obtain desired compounds (3a-3g). The structures of these compounds have been established by IR, 1H-NMR, Mass spectral and elemental analysis. These synthesized compounds (3a-3g) were evaluated for their antimycobacterial activity against M. tuberculosis H37Rv strain. Results: All the synthesized compounds (3a-3g) exhibited antimycobacterial activity and were compared to reference drugs Streptomycin (MIC value of 6.25μg/mL), INH (MIC value of 3.125μg/mL) and pyrazinamide (MIC value of 3.125μg/mL). Compounds 3c and 3e exhibited the most promising antimycobacterial activity. Conclusion: All the title compounds were synthesized and exhibited promising antimycobacterial activity against M. tuberculosis H37Rv strain.
Keywords: mannich bases